Relative Age Effect on Brazilian male elite futsal athletes according to playing position and performance by goals scored on Brazil National Futsal Leagues - Henrique de Oliveira Castro; Samuel da Silva Aguiar; Filipe Manuel Clemente; Ricardo Franco Lima; Gustavo De Conti Teixeira Costa; Lucas Savassi Figueiredo; Vivian de Oliveira; Sérgio Adriano Gomes (Universidade Estadual Paulista (UNESP), 2021)
Abstract Introduction: The relative age effect is prevalent in different elite team sports. However, little is known about this phenomenon in high-level adult male futsal players. Aim: The present study aimed to investigate the prevalence of relative age effect in Brazilian male elite futsal players, and its relationship with playing position and goals scored on Brazil National Futsal Leagues (BNFL) from 2016 to 2020. Methods: The distribution of birth dates, playing positions, and goals scored by male participants of the Brazil National Futsal Leagues were analyzed. Chi-squared tests were used to analyze the birth dates distribution based on quarters and semesters of the year, according to playing position (defender, winger, pivot, and goalkeeper) and scoring performance (high and low). Results: The overall analysis indicated that the relative age effect is prevalent on the pool of athletes analyzed. However, this effect was position-dependent, since relatively older athletes were overrepresented only in wingers and defenders playing positions. On the other hand, scoring performance was not associated with the relative age effect, since this effect was found in both performance levels. Conclusion: Relative age effects are prevalent in Brazilian male elite futsal athletes, especially for defenders and wingers. Considering the high level of competitiveness for spots in elite futsal teams, coaches and sports administrators must be educated about the prevalence of the relative age effect in this sporting context. This is necessary in order to reduce the inequalities generated by age categories based on arbitrary cut-off dates, which may reduce potential talent loss.